1999
DOI: 10.1046/j.1365-2044.1999.00893.x
|View full text |Cite
|
Sign up to set email alerts
|

Dosage of neostigmine for reversal of rocuronium block from two levels of spontaneous recovery

Abstract: SummarySpontaneous recovery, and recovery following neostigmine 20, 35 or 50 mg.kg ¹1 administered at 10 or 25% of recovery of the first twitch of the train-of-four, was assessed in 80 patients after rocuronium administration under continued isoflurane anaesthesia. In an additional 40 patients, isoflurane administration was discontinued and neostigmine 35 or 50 mg.kg ¹1 was given at 10 or 25% recovery. The administration of neostigmine reduced the recovery times significantly. A neostigmine dose of 20 mg.kg ¹1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 24 publications
1
20
1
Order By: Relevance
“…However, neostigmine 0.07 mg/kg is more likely to be associated with side effects than are neostigmine doses of 0.03 mg/kg and 0.05 mg/kg. Viby-Mogensen et al advocated that administration of anticholinesterases not take place before 25% recovery was achieved, because reversal of long-lasting, nondepolarizing muscle relaxants might lead to incomplete recovery of neuromuscular block [9]. However, neuromuscular block from moderate doses of the medium-lasting muscle relaxant rocuronium can rapidly be reversed following neostigmine administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, neostigmine 0.07 mg/kg is more likely to be associated with side effects than are neostigmine doses of 0.03 mg/kg and 0.05 mg/kg. Viby-Mogensen et al advocated that administration of anticholinesterases not take place before 25% recovery was achieved, because reversal of long-lasting, nondepolarizing muscle relaxants might lead to incomplete recovery of neuromuscular block [9]. However, neuromuscular block from moderate doses of the medium-lasting muscle relaxant rocuronium can rapidly be reversed following neostigmine administration.…”
Section: Discussionmentioning
confidence: 99%
“…Group 3 (n = 20) was used as the control group, with spontaneous recovery from neuromuscular block. Doses of neostigmine 0.03 mg/kg and 0.05 mg/kg were reported to safely antagonize rocuronium block [9].…”
Section: Methodsmentioning
confidence: 97%
“…For example, McCourt et al found no difference between 35 and 50 lgÁkg -1 in time to full recovery. 24 In another study, the time course of effect for 30, 40, and 55 lgÁkg -1 was very similar. 25 Neostigmine thus provides only partial recovery.…”
mentioning
confidence: 87%
“…4 Although there are reports of antagonism of rocuronium block with neostigmine, these have generally examined the influence of the dosage or the timing of administration of the anticholinesterase. [5][6][7] The aim of the present study was to examine the effect of the sevoflurane on the antagonism of rocuronium by neostigmine, and compare it with the effects of isoflurane, and intravenous anesthesia. …”
mentioning
confidence: 99%
“…4 Although there are reports of antagonism of rocuronium block with neostigmine, these have generally examined the influence of the dosage or the timing of administration of the anticholinesterase. [5][6][7] The aim of the present study was to examine the effect of the sevoflurane on the antagonism of rocuronium by neostigmine, and compare it with the effects of isoflurane, and intravenous anesthesia. Patients and methods One hundred and twenty three ASA I or II patients (of whom three were replacement patients), aged between 18 and 65 yr, and scheduled to undergo elective body surface or orthopedic surgery lasting longer than 30 min were recruited into the study following their written informed consent and Research Ethics Committee approval.…”
mentioning
confidence: 99%